River North Greenway: strategizing a generation 4 greenway as a dynamic mosaic - Murman, Christie (Kansas State University, 2010)
Greenways are an evolving landscape form, adapting to the needs of humans through time. Rooted in the work of Frederick Law Olmsted, greenways have progressed to become an international movement. Throughout this progression, three generations of greenways are recognizable—Generation 1: Parkways and Boulevards, Generation 2: Trail-Oriented Recreation, Generation 3: Multi-Objective (Searns 2002). Given the ideals of sustainability that drive our contemporary society, a fourth generation is poised to emerge. Responsive to sustainability, the fourth generation will be envisioned as a holistic system, structured within the frameworks of landscape ecology theory as developed by Richard Forman, and expanded with the progressive thinking of Jack Ahern and Kristina Hill. River North Greenway in Denver, Colorado is prime for transformation. Compromised by its industrial context, yet vitalized through the flow of the South Platte River and the infill development growing up the valley from Downtown Denver, River North will be re-defined as a holistic system. Utilizing the spatial pattern and process dynamics that define ecological theory (Forman 1996), abiotic, biotic, and cultural functions (Ahern 2007) will become the fundamental elements in strategizing the greenway as a multi-scalar dynamic mosaic (Hill 2005). River North Greenway will become a complexity of cultural activity and abiotic and biotic health, balancing programmed space with the enhancement and restoration of ecosystems. It will transform the City of Denver, enriching the connection between the city and its river, the people and nature. With its rich history and present potential, River North can become a timeless piece of Denver’s urban landscape, shaping meaningful human experiences and preserving nature within the built environment for future generations. In turn, it can propel the greenway movement towards a fourth generation.
Keywords: Landscape architecture; River North Greenway; South Platte River; Greenway planning and design; Landscape ecology; Landscape Architecture (0390)